Q: How do you write an equivalent addition expression for a subtraction expression?

Write your answer...

Submit

Still have questions?

Related questions

A - B = A + (-B) A - B = A + (-B) A - B = A + (-B) A - B = A + (-B)

800 + 90 + 4 - 1 = 893

78 + yz = yz + 78

to come up with the total

3-3=0

If you have x+-y=z, than you can turrn it into subtraction: x-y=z. x+-y=x-y

What you write for PEMDAS is P (parenthesis) E exponents M multiplication D division A addition S subtraction!

467 + 1

6000 + 100 + 20 + 5

2000+700+80+4

When you have an algebraic expression, the term is "reducing" the expression when you write the expression in fewer terms or smaller multiples.

24 is 3 x 8 If you have to use both numbers twice: 24 is sqrt(3 x 3 x 8 x 8)